Green economy reader : lectures in ecological economics and sustainability - Shmelev, Stanislav (Springer, 2017)
"State of the art in sustainability thinking, inspired by interdisciplinary ideas of ecological economics. This book is focusing on sustainability pathways, new economic theory, democracy and institutions, multidimensional assessment of sustainability, macroeconomic modelling and policies, climate change and renewable energy, resource flows and circular economy, regenerative cities, environmental conflicts and values. It will be helpful for MSc and PhD students in Economics, Management, Environmental Change, Ecological Economics, Development Economics, Sustainability and practitioners in business, international and nongovernmental organizations. Rich, diverse and thought provoking collection of top level contributions, it will help to facilitate the transition towards sustainability and educational reform"- Resumé vydavatel
Keywords: environmentální ekonomie; ekologie -- ekonomické aspekty; udržitelný rozvoj -- ekonomické aspekty; environmental economics; ecology -- economic aspects; sustainable development -- economic aspects; elektronické knihy; sborníky; electronic books; papers of several authors